Linguocultural Adaptation of Migrants in the Context of Educational Migration to Russia - Elʼnara M. Dumnova; Victoria N. Mukha (Гуманитарный вектор, 2022)
International educational migration is an integral element of the modern world, which actualizes the problem of adaptation of educational migrants. Linguocultural adaptation is especially interesting, because it determines the strategy of adaptation and the result of the further integration of the migrant in the new society. The purpose of the article is to study the linguistic and cultural adaptation of the subjects of international academic migration in the context of the new space of everyday life. The empirical basis of the research was the results of an interregional study within the framework of a qualitative approach using the methods of in-depth and semi-structured interviews, conducted in March-April 2021. 20 informants were interviewed. The case study method became the tactic of the qualitative approach, the Krasnodar Territory and the Novosibirsk Region acted as local cases. In the Krasnodar Territory, people from Arab-Muslim countries were interviewed, students from China were interviewed in the Novosibirsk Region. The analysis of the interviews allowed us to identify the factors that determine the success of linguocultural adaptation of educational migrants, as well as the main difficulties in the process of formation of language competence and, consequently, linguocultural adaptation of both students from Arab-Muslim countries and Chinese students. The research showed that attention to the ethno-national characteristics of foreign students, to their system of motivation in organizing the learning process, inclusion in the culture of the host community, contribute to faster and more successful linguocultural adaptation. It was concluded that new types of identity are determined in the process of linguocultural adaptation by the degree of empathy of the migrants’ native culture. The research results can be used in the formation of adaptation programs for educational migrants in Russian universities.